2001
DOI: 10.4049/jimmunol.166.12.7625
|View full text |Cite
|
Sign up to set email alerts
|

The Prevention and Treatment of Murine Colitis Using Gene Therapy with Adenoviral Vectors Encoding IL-10

Abstract: IL-10-deficient (IL-10−/−) mice develop colitis with many similarities to Crohn’s disease. Daily IL-10 injections have a short systemic half-life and are unable to induce complete remission in IL-10−/− mice with established disease. In this paper, we investigate the duration, potency, and immunogenicity of gene therapy using an adenoviral vector encoding murine IL-10 (AdvmuIL-10). A single systemic injection of AdvmuIL-10 was sufficient not only to prevent the onset of colitis for at least 10 wk but also to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…This agrees with our previous observation that serum mIL-10 levels are raised for approximately 1 week after AdvmuIL-10 administration in IL-10 À/À mice. 23 Previous studies have demonstrated low-level colonic transgene expression after systemic adenoviral vector delivery; 18,19 however, there was no difference in the levels of IL-10 detected in colon homogenates from AdvmuIL-10 or control treated mice with TNBS colitis.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…This agrees with our previous observation that serum mIL-10 levels are raised for approximately 1 week after AdvmuIL-10 administration in IL-10 À/À mice. 23 Previous studies have demonstrated low-level colonic transgene expression after systemic adenoviral vector delivery; 18,19 however, there was no difference in the levels of IL-10 detected in colon homogenates from AdvmuIL-10 or control treated mice with TNBS colitis.…”
Section: Discussionmentioning
confidence: 90%
“…29 Finally, in this study we did not assess the host anti-adenovirus response, which may shorten the duration of transgenic IL-10 expression. However, in other animal models, we 23 and others 30,31 have shown that the delivery of immunoregulatory genes is able to suppress the development of antiadenoviral antibodies resulting in extended transgene expression.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations